EFFECTS OF SUPPLEMENTATION OF GUAVA JUICE (Psidium guajava L.) TO THE ANDROMED DILUENT ON THE QUALITY OF INDIGENOUS CHICKEN SEMEN STORED AT ROOM TEMPERATURE - F. K. Nisaa; F. Andri; M. N. Ihsan; N. Isnaini (Journal of Animal and Plant Sciences, 2023)
Indigenous chicken serve as a highly valuable germplasm for the development of the poultry industry in Indonesia. They also play an important role in rural communities as a source of meat, eggs, and additional income. This study evaluated the semen quality of indigenous chicken in the Andromed diluent supplemented with different levels of guava juice during storage at room temperature (24-25oC) for 0, 30, 60 or 90 minutes. The semen was collected from an indigenous rooster, aged 2.5 years with body weight of 2.5 kg. A total of 10 ejaculates were collected from this rooster; the frequency of semen collection was twice a week. The semen was diluted in the Andromed diluent supplemented with guava juice at the level of 0 (control), 2, 4, or 6%. Evaluation of semen quality parameters included sperm motility, live sperm, and morphologically abnormal sperm. Data were analyzed by using two-way analysis of variance followed by Duncan Multiple Range Test to compare means. Results showed that regardless of storage time, the use of 6% guava juice had significantly higher (P<0.05) sperm motility and live sperm, but lower abnormal sperm as compared to other treatments. It was also found that regardless of guava juice level, the longer storage time continually decreased (P<0.05) the sperm motility and live sperm, but increased (P<0.05) abnormal sperm. Results also showed that there were interaction effects (P<0.05) between the level of guava juice and storage time on the sperm motility and live sperm. This study provides evidence that the addition of 6% guava juice to the Andromed diluent results in better semen quality for artificial insemination up to 60 minutes of storage at room temperature.
Keywords: Andromed; guava juice; room temperature; semen quality; indigenous chicken